Minnesota Impulse Disorders Interview (MIDI): Validation of a structured diagnostic clinical interview for impulse control disorders in an enriched community sample - Chamberlain, Samuel R. (Psychiatry Res, 2018)
BACKGROUND: Disorders of impulsivity are common, functionally impairing, and highly relevant across different clinical and research settings. Few structured clinical interviews for the identification and diagnosis of impulse control disorders exist, and none have been validated in a community sample in terms of psychometric properties. METHODS: The Minnesota Impulse control disorders Interview (MIDI v2.0) was administered to an enriched sample of 293 non-treatment seeking adults aged 18–35 years, recruited using media advertisements in two large US cities. In addition to the MIDI, participants undertook extended clinical interview for other mental disorders, the Barratt impulsiveness questionnaire, and the Padua obsessive-compulsive inventory. The psychometric properties of the MIDI were characterized. RESULTS: In logistic regression, the MIDI showed good concurrent validity against the reference measures (versus gambling disorder interview, p < 0.001; Barratt impulsiveness attentional and non-planning scores p < 0.05), and good discriminant validity versus primarily non-impulsive symptoms, including against anxiety, depression, and obsessive-compulsive symptoms (all p > 0.05). Test re-test reliability was excellent (0.95). CONCLUSIONS: The MIDI has good psychometric properties and thus may be a valuable interview tool for clinical and research studies involving impulse control disorders. Further research is needed to better understanding the optimal diagnostic classification and neurobiology of these neglected disorders.